The Journey of Business Opportunity Evaluation: When and Why Does Opportunity Novelty Promote Vs. Inhibit Opportunity Adoption? - Lin, Lin; Lin, Yanan; Lin, Song (Frontiers in Psychology, 2021)
As a typical characteristic of entrepreneurial opportunities, novelty is essential for firms to establish and maintain a sustainable competitive advantage under the current complex and dynamic business environment. However, why is it that some entrepreneurs adopt novel opportunities but others do not. Little is known about the precise nature of cognitive evaluation for opportunity novelty. Drawing upon information processing theory and construal level theory, we propose that the effects of opportunity novelty on adoption decisions depend on entrepreneurs’ construal level through which information is processed. We design an experiment and find partial support for our hypotheses. Results indicate that entrepreneurs using a low-level construal perceive more risk for opportunity novelty, which in turn decreases the possibility of opportunity adoption. Meanwhile, opportunity novelty also positively influences entrepreneurs’ creativity perception, which in turn increases the possibility of opportunity adoption. But construal level does not play any role in this evaluation path. Taken together, the findings improve our understanding of “how entrepreneurs evaluate an opportunity based on its objective characteristics” by providing empirical insights into the cognitive information processing process from opportunity novelty to adoption. Additionally, we discuss implications for entrepreneurial practice and future research.